Analisis Pengaruh Harga CPO, Tingkat Inflasi Dan Nilai Tukar Rupiah Terhadap Harga Saham Perusahaan Sub Sektor Perkebunan Kelapa Sawit Tahun 2017-2021 - Rini Porwati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to determine the influence of CPO prices, inflation rates and the Rupiah exchange rate on share prices of companies in the palm oil plantation sub-sector listed on the Indonesia Stock Exchange in 2017-2021. The type of research used is quantitative research with the data source used is secondary data. The sample in this research was 12 oil palm plantation companies using a purposive sampling technique, namely a sampling technique that sets certain criteria. This research uses panel data regression with the selected model, namely the random effect model. The classical assumption tests used include normality tests and multicollinearity tests with t-statistic hypothesis tests, F-statistics and coefficient of determination. The partial research results show that CPO prices have a significant effect on stock prices, the inflation rate has a significant effect on stock prices and the rupiah exchange rate has a significant effect. Meanwhile, the research results simultaneously show that CPO prices, inflation rates and the rupiah exchange rate have a significant effect on stock prices.